Soil Health and 4R: What Practices Are Working?. Issue 1 (29th December 2020) - Flis, Sally; Bowman, Maria
Abstract : Soil health and 4R nutrient stewardship practices work together on farms to reduce nutrient losses. Farmers who work with the Soil Health Partnership (SHP) are adopting both at the same time. In the summer of 2020, SHP asked farmers about nutrient management practices on their SHP research fields between 2014 and 2019. This article focuses on the farmer‐reported nutrient management practices from that survey in years where corn was grown on the SHP research field from 105 farms that reported nutrient management practices in at least one corn year. Earn 0.5 CEUs in Nutrient Management by reading this article and taking the quiz at www.certifiedcropadviser.org/education/classroom/classes/913 .